Accounting information quality moderates the effect of dividends on investment decisions: Evidence in Vietnam - Quoc Trung Nguyen Kim (Cogent Economics & Finance, 2023)
The author specifies the pivotal role of accounting information quality in moderating the influence of dividends on the investment decisions of listed firms in Vietnam from 2009 to 2020. In this study, the significant dependence of investment on dividends is proved by the Two-Step System Generalized Method of Moments. The key findings show that dividends and investment decisions have a statistically significant negative relationship. The relationship is clarified based on agency theory, asymmetric information theory, and signaling theory, which are used in low-information-transparency markets such as the Vietnamese market. Primarily, the role of a moderating factor could mitigate the negative relationship above.
Keywords: D25; D82; E22; G11; L21; 330; accounting information quality; agency theory; asymmetric information theory; dividends; investment; SGMM; signaling theory; Vietnam